Thermoset and Thermoplastic Elastomeric Chain Comparative Strength: An In Vitro Study - Ari Triwardhani, - (WoltersKluwerMedknow Publications, 2019)
Aim: Technology in the field of orthodontic has experienced many developments in the last two decades. The ultimate goal of orthodontic treatment is to provide continuous light pressure to get orthodontic tooth movement with minimum side effects. Elastomeric chains are commonly used materials for moving teeth and closing space. The strength of elastomeric chain results in a tendency for better elastomer selection. Some factories make elastomeric chains with thermoplastic and thermoset materials with thermoset material claims having strength resistance for longer periods of time. The aim of the study was to compare the degradation strength between thermoplastic and thermoset elastomeric chain. Materials and Methods: This was a true-experimental laboratory study (in vitro study). The sample comprised open-type elastomeric chains (power chain) with clear transparent color thermoplastic material, which include original power chain, plastic chain and thermoset material generation II, and memory chain. The samples were divided into four groups (n = 5): 24 h, 7, 14, and 21 days. Independent samples t tests and analysis of variance (ANOVA) were performed to analyze the data. Results: There was significant dissimilarity between thermoplastic and thermoset elastomeric chain material in strength.Thermoplastic elastomeric chains decreased by 60.84%–65.51% and thermoset elastomeric chain reached 36.28%–58.80% within 21 days in artificial saliva solution. Conclusion: There was dissimilarity between the Chermoplastic and thermoset elastomeric chain materials in force decay due to excessive early withdrawal forces in the elastomeric chains of thermoplastic materials with a more rigid material than the thermoset elastomeric chains of the thermoset material.